Obliczanie Trwałych Pionowych Deformacji Toru w Zależności od Typu Nawierzchni Kolejowej - S. Bonkowicz-Sittauer (Engineering Transactions, 1971)
The source of deformations of a railway track are stable deformations of the subsurface. To a large degree these depend on the rigidity of the rail, which is the most expensive element of the track. On the other hand, the rate of deformation growth determines the frequency and scope of track repairs. Therefore the correct selection of rail type is of economic importance. In this paper is presented a method of «optimum» selection of the type of rail having regard to the process of the formation of stable vertical deformations. A mathematical-mechanical model of the track is constructed, enabling determination of the magnitude of deformation as a function of the rigidity of the rail. Such functions are determined for different conditions of support. Subsequently, the «optimum» rail type is found by means of the means of the method suggested in the paper. This is found to be very similar to the UIC-60 type, which is at present considered in many countries to be the most advisable for high volume of traffic. The calculations described in this paper were carried out numerically on the ODRA-1204 computer. In the remaining part of the paper, the mathematical and mechanical model of the track has been transformed in order to make possible the simulation of the process of deformation growth under the consecutive loading cycles. Moreover, the method has been presented of numerical determination of the track deformation function dependent on the rail rigidity, the sleeper spacing and supporting, the magnitude of a single force and the number of its application.